Essay Grading System (EGS) / Elaiyakumaran Subramaniam - Elaiyakumaran, Subramaniam (2004)
As a part of my graduation exercise, it is required to develop a system for the Degree of Bachelor in Computer Science and Information Technology, University of Malaya. The system is intended to develop an Automated Essay Grading System (EGS). The EGS hopes to overcome the manual marking that are done for many years. The EGS's aim is to give a fast response and marks to the questions that are answered. The literature review gives an overview of the marking system and findings of various researches and technology in the effectiveness of the Automated Essay Grading System. Some of the literature review surveys done are examined and their features compared. In this project, sources were collected from various part including the internet, books, and the senior projects. The Automated Essay Grading System developed by using V-model as a foundation of the systems process flow. The selection of both hardware and software are vital to ensure the success of a system. Criteria such as capability, credibility cost, speed and size of memory have been emphasized to ensure the bardware selected meet the requirement of the system to be developed. System design is very crucial in a system development process as it plays a major role in determining the success of the systems. There are two kinds of user interfaces - the student interface and the marking system (teachers). In conclusion, the system will help teachers to organize their student's exam in an appropriate way. Whereas, the students could learn and practice the history subject efficiently.